Modelling of a five-phase induction motor with quasi-trapezoidal air-gap flux density distribution - Blecharz, Krzysztof; Ryndzionek, Roland (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
This article proposes a practical and flexible modelling approach for a five-phase squirrel-cage induction motor that explicitly accounts for the shape of the air-gap magnetic flux density distribution. Two motor configurations are analysed and compared: one with a sinusoidal air-gap flux distribution and another with a quasi-trapezoidal distribution obtained through third-harmonic voltage injection. The proposed modelling framework is based on vector space decomposition into two orthogonal mathematical planes and is implemented using standard components available in the PLECS simulation environment. Finite element analysis is used to support the selection of model parameters and to evaluate the influence of harmonic injection on the air-gap flux distribution. The developed models are verified by simulations and laboratory experiments carried out on the five-phase induction motor. The results confirm that a quasi-trapezoidal air-gap flux distribution enables the second vector plane to contribute to torque production and leads to improved magnetic flux utilisation. The proposed approach provides a clear and flexible tool for the analysis and development of control strategies for five-phase induction motor drives.